The equation 4(x+3) = 0 has to be solved for x.

4(x+3) = 0

=> x + 3 = 0

=> x = -3

**The solution of 4(x+3) = 0 is x = -3.**

Due to the zero product principle, this problem has 1 answer.

The zero-product principle says that when multiplying two or more terms to get 0, one (or more) must equal zero.

4 can never equal zero, so in this case, the (x+3) must equal zero.

It is simple to solve this:

x+3=0 Subtract 3 from both sides and...

x=-3 Voila!

x=-3 is your answer.

4(x+3) = 0

Distribute the 4 to the x and the 3. (Multiply)

4x+12=0

Subtract 12 on both sides to isolate the variable.

4x=-12

Divide both sides by 4 to isolate x.

x=-3

4(x+3) = 0

Distribute 4

4x + 12 =0

subtract 12

4x = -12

divide by 4

x = -3

4(x+3) = 0

Distribute the 4:

4x + 12 =0

subtract the 12:

4x = -12

divide by 4

x = -3

You are solving for x but it says it equals to 0, well because of that you need to distribute the variable first

4(x+3) = 0

4x+12=0

Now instead of the 0 you can move the 12 over to isolate the variable

then divide by 4

x=-3

4 ( x + 3 ) = 0

First distribute

By distributing, your equation should look like

**4x + 12 = 0 **now subtract 12 on both sides to get " x " alone

By subtracting, your equation should look like

**4x = -12 **Now divide 4 on both sides

By dividing, your equation will look like

**x = -3 **which is your answer

4 (x + 3) = 0

We know that either the left factor or the right factor has to equal zero. Since 4 can never equal zero, we only have to set x + 3 = 0

Solving for x, we get that x = -3.